A kind of CNTs@PDA@HsGDY nanofiber-derived microwave absorber and its preparation method
By introducing nitrogen-doped carbon and hydrogenated graphite alkyne layers on the surface of the carbon nanotube, CNTs@PDA@HsGDY nanofiber derivatives with three-layer core-shell structures are solved, and the absorption performance of existing carbon nanotube absorbing materials is achieved. The absorption performance of lightweight, thin layer, wide band and high absorption strength is achieved. It is suitable for radio communication and radar stealth technology.
Patent Information
- Application Number
- CN202310900651.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-07-11
- Estimated Expiration
- 2043-07-21
AI Technical Summary
The existing carbon nanotube absorbing materials have problems such as complex preparation process, difficulty in uniform distribution and regulation of metal particles, and difficulty in balancing light and wide-band absorption and high absorption intensity.
CNTs@PDA@HsGDY nanofiber derivatives with three-layer core-shell structures are introduced into the carbon nanotube surface in turn to form multiple heterogeneous interfaces to enhance dielectric loss and impedance matching performance. The preparation methods include ultrasonic dispersion, oxidation and autopolymerization of dopamine hydrochloride, 1,3,5-triacetylene benzene Glaser-coupling reaction and vacuum carbonization treatment.
It realizes lightweight, thin layer, wide band and high absorption intensity absorption performance, simplifies the preparation process, improves the stability and absorption effect of the material, broadens the effective absorption bandwidth, and is suitable for radio communication and radar stealth technology.
Smart Images

Figure CN116949601B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of microwave absorbing materials, and particularly relates to a CNTs@PDA@HsGDY nanofiber-derived microwave absorber and a preparation method thereof. Background Art
[0002] Due to their excellent dielectric properties, good composite characteristics, and special microstructures, carbon materials have received extensive attention in the field of electromagnetic wave absorption (Chinese patents CN216600681U, CN110950320B).
[0003] Carbon nanotubes (CNTs) are similar to one-dimensional tubular structures obtained by curling graphene sheets. This special structure endows CNTs with a high specific surface area, high porosity, anisotropy, and long-range dielectric loss, which have made them widely studied as microwave absorbers. However, for pure CNTs, problems such as single component, lack of multiple electromagnetic wave loss mechanisms, and too high dielectric constant reducing impedance matching limit the further application of CNTs.
[0004] Currently, the research on the improvement and performance enhancement of CNT microwave absorbing materials mainly focuses on three aspects:
[0005] 1. Composites with other functional components, including Chinese patent CN111205819B which provides a carbon nanotube-aluminum nitride microwave absorber and its preparation method, a carbon nanotube-aluminum nitride composite microwave absorbing material and its application, including carbon nanotubes and aluminum nitride; Chinese patent CN113249819B which provides a carbon nanotube-nano Fe3O4-polyimide composite fiber and its preparation method;
[0006] 2. In-situ growth of CNTs on the surface of other materials. For example, Chinese patent CN109880591B provides a porous carbon@carbon nanotube microwave absorbing material and its preparation method, and Chinese patent application CN111944482A provides a preparation method for a sea urchin-like carbon nanotube-coated Co particle composite microwave absorbing material;
[0007] 3. Filling other components inside CNTs. For example, Chinese patent CN104945759B provides a cerium-doped nickel-zinc ferrite-filled carbon nanotube composite microwave absorber and its preparation, and Chinese patent CN102627834B provides a preparation method for a chitosan-modified barium ferrite-filled multi-walled carbon nanotube / poly-3-methylthiophene composite microwave absorbing material.
[0008] Although the above composite microwave absorbing materials have improved in performance, they have problems such as complex preparation processes, and even difficulty in regulating the uniform distribution of metal particles. At the same time, it is impossible to find a balance among light weight, wide-band absorption, and high absorption intensity.
[0009] Based on the current R & D background, the present invention aims to provide a new composite wave - absorbing material. Summary of the Invention
[0010] The research team of the present invention previously applied for an invention titled "A New Type of One - Dimensional Tubular Carbon - Based Wave - Absorbing Agent and Its Preparation Method", with the application number: 202310809505.1. It uses carbon nanotubes as a template and coats hydrogenated graphdiyne (HsGDY) on its surface, forming a double - layer core - shell tubular structure. As a wave - absorbing agent, although the wave - absorbing performance of this product has been optimized compared with existing composite wave - absorbing materials, in order to balance its loss ability and impedance matching performance while reducing the material density and enriching the types of wave - absorbing agents to make this technology more competitive in application, the application team of the present invention further optimized the technology, a CNTs@PDA@HsGDY nanofiber - derived wave - absorbing agent and its preparation method, that is, a multi - shell - layer - structured one - dimensional wave - absorbing agent containing hydrogenated graphdiyne components and its preparation method.
[0011] Concept of the present invention:
[0012] In view of the problems existing in the existing composite microwave absorbing materials, the research team of the present invention previously regulated the dielectric parameters and optimized the absorption performance by optimizing the composition and designing the structure. Still, the highly concerned carbon nanotubes were selected as the template, and hydrogenated graphdiyne was simultaneously introduced for optimization to design a new one-dimensional microwave absorber. Here, the new application of hydrogenated graphdiyne discovered by this R & D team was fully utilized - it can be used to prepare microwave absorbers. By introducing hydrogen atoms into the benzene ring for molecular modification, a perfect π-type conjugated system (a conjugate formed by four types of carbon-carbon bonds) was formed, which has a high specific surface area, a wide interplanar spacing, high crystallinity, a uniformly dispersed pore configuration, a tunable electronic structure and semiconductor characteristics, good electrical conductivity and a large number of active sites. It not only contains a large number of alkyne bonds but also has a unique hierarchical porous structure, which can provide a path for electron transport, effectively enhancing the dielectric loss of the material and belonging to a functional component. Therefore, in order to further optimize the R & D results, the present invention intends to add a layer of polydopamine between the carbon nanotubes and the hydrogenated graphdiyne layer under the design principle of "light weight, thin thickness, wide frequency band, and strong absorption", introducing multiple heterogeneous interfaces to enhance interface polarization and improve the loss ability. At the same time, due to the combined action of hydrogen bonds and π-π stacking, polydopamine forms a dense film with remarkable stability. The existence of this dense film is beneficial to improving the stability of the material. After high-temperature carbonization, polydopamine is converted into a nitrogen-doped carbon layer, which has a rich pore structure, significantly increasing the specific surface area of the material and having a better microwave absorption effect than the pure carbon layer; and after the nitrogen-doped carbon layer is formed by carbonizing polydopamine, there are a large number of defects, which will further cause dipole polarization, facilitating the dissipation of microwaves and contributing significantly to the improvement of the microwave absorption performance of the material. Therefore, the present invention intends to use hydrogenated graphdiyne combined with carbon nanotubes and nitrogen-doped carbon to prepare a new type of microwave absorber.
[0013] Based on the above inventive concept, to achieve the above object, the technical solution provided by the present invention is:
[0014] A CNTs@PDA@HsGDY nanofiber derivative, characterized in that: it presents an overall three-layer core-shell structure, successively from the inside to the outside being carbon nanotubes (CNTs), a nitrogen-doped carbon (NC) layer, and a hydrogenated graphdiyne (HsGDY) layer. Its inner diameter and length are the same as those of the selected carbon nanotubes. The thickness of the nitrogen-doped carbon layer is 60 - 85 nm, and the thickness of the hydrogenated graphdiyne layer is 5 - 13 nm;
[0015] The carbon nanotubes are single-walled or multi-walled carbon nanotubes with carboxyl or hydroxyl groups on the surface; among them, the carboxyl group content is less than 1.5 wt%, and the hydroxyl group content is higher than 2 wt%.
[0016] The preparation method of the above CNTs@PDA@HsGDY nanofiber derivative is characterized by including the following steps:
[0017] 1) Ultrasonically disperse carbon nanotubes uniformly in a buffer solution with pH = 8.3 - 8.7 to obtain suspension A;
[0018] The carbon nanotubes are single-walled or multi-walled carbon nanotubes with carboxyl or hydroxyl groups on the surface; among them, the carboxyl content is higher than 1.5 wt%, and the hydroxyl content is higher than 2 wt%;
[0019] 2) Under magnetic stirring, add a buffer solution containing dopamine hydrochloride with pH = 8.3 - 8.7 to suspension A obtained in step 1), react at room temperature, and after the reaction is completed, centrifuge, wash with ethanol, and vacuum dry to obtain CNTs@PDA nanotubes;
[0020] 3) Mix the CNTs@PDA nanotubes obtained in step 2) with solvent I and solvent II, and ultrasonically disperse them uniformly to obtain suspension B;
[0021] Solvent I is tetrahydrofuran or pyridine;
[0022] Solvent II is trimethylamine or triethylamine;
[0023] 4) Under the protection of inert gas, add 1,3,5-triethynylbenzene, catalyst I and catalyst II to suspension B obtained in step 3), react at room temperature with stirring, and after the reaction is completed, centrifuge, wash with ethanol, and vacuum dry to obtain CNTs@PDA@HsGDY nanofibers;
[0024] Catalyst I is a palladium catalyst in the form of a complex;
[0025] Catalyst II is a cuprous halide catalyst;
[0026] 5) Vacuum carbonize the CNTs@PDA@HsGDY nanofibers obtained in step 4) to obtain the product CNTs@PDA@HsGDY nanofiber derivative - CNTs@NC@HsGDY.
[0027] Furthermore, in step 1), the buffer solution is a Tris hydrochloride buffer solution with pH = 8.3 - 8.7;
[0028] In suspension A, the mass concentration of carbon nanotubes is 0.5 - 1 mg / mL.
[0029] Furthermore, in step 2), the buffer solution used is a Tris hydrochloride buffer solution with pH = 8.3 - 8.7; the mass concentration of dopamine hydrochloride is 1 - 3 mg / mL; the mass ratio of carbon nanotubes to dopamine hydrochloride is 1:2 - 5;
[0030] The reaction time at room temperature is 24 - 48 h;
[0031] After the reaction is completed, wash with ethanol.
[0032] Further, in step 3), the volume ratio of solvent I to solvent II is 1:1 to 3;
[0033] In suspension B, the mass concentration of CNTs@PDA nanotubes is 0.1 - 0.5 mg / mL.
[0034] Further, in step 4), the catalyst I is bis(triphenylphosphine)palladium dichloride or tetrakis(triphenylphosphine)palladium;
[0035] The catalyst II is cuprous iodide, cuprous bromide or cuprous chloride;
[0036] The molar ratio of 1,3,5 - triethynylbenzene, catalyst I and catalyst II is 3∶1∶1;
[0037] The mass ratio of 1,3,5 - triethynylbenzene to CNTs@PDA nanotubes is 1:8 to 10;
[0038] React at room temperature for 48 - 64 h under magnetic stirring;
[0039] After the reaction is completed, wash with ethanol.
[0040] Further, step 5) is specifically:
[0041] Vacuum carbonize the CNTs@PDA@HsGDY nanofibers obtained in step 4) in a tube furnace at 600 - 900 °C for 1 - 3 h, and control the heating rate to be 1 - 5 °C / min (if the heating rate is too fast, the product structure will be damaged, defects will be formed, and the performance will be affected; if the heating rate is too slow, the production efficiency will be affected), to obtain the product CNTs@PDA@HsGDY nanofiber derivative - CNTs@NC@HsGDY.
[0042] In addition, the present invention also provides the application of the above CNTs@PDA@HsGDY nanofiber derivative CNTs@NC@HsGDY as a microwave absorbing agent.
[0043] And, a device with radar stealth function, which is characterized in that: it uses the above CNTs@PDA@HsGDY nanofiber derivative CNTs@NC@HsGDY as a microwave absorbing agent for filling.
[0044] Advantages of the present invention:
[0045] 1. The present invention uses carbon nanotubes as a template. By successively carrying out the oxidative self-polymerization reaction of dopamine hydrochloride in a weakly alkaline solution and the Glaser-coupling reaction of 1,3,5-triethynylbenzene on the surface of CNTs, a precursor is obtained. After vacuum carbonization, the CNTs@PDA@HsGDY nanofiber derivative - CNTs@NC@HsGDY is prepared. This scheme innovatively introduces a new type of carbon material, hydrogenated graphdiyne (HsGDY), as the shell layer. Its good electrical conductivity is beneficial to enhancing the electrical conductivity loss of the material. However, in order to overcome the surface skin effect and ensure reasonable electrical conductivity of the material, the HsGDY shell layer should not be too thick, and thickness control is the key, which should be controlled within 5 - 13 nm. In order to facilitate good coating of polydopamine, the surface of the carbon nanotubes should be hydrophilic. Therefore, single-walled or multi-walled carbon nanotubes with carboxyl or hydroxyl groups on the surface are selected (wherein, the carboxyl content is higher than 1.5 wt%, and the hydroxyl content is higher than 2 wt%). The polarization relaxation caused by multiple heterogeneous interfaces is beneficial to enhancing the interfacial polarization. The N doping in the carbon material promotes the generation of dipole polarization. Therefore, the product of the present invention can effectively improve the overall impedance matching and attenuation characteristics of the material, broaden the effective absorption bandwidth of a single-component material, obtain significant electromagnetic wave absorption properties, and realize the controllable preparation of a new type of one-dimensional wave-absorbing material with the characteristics of "light, thin, wide, and strong".
[0046] 2. The preparation method of the target product of the present invention is simple. There is a situation of uneven distribution of metal particles, and its morphology and wave-absorbing performance can be effectively regulated by changing the dosage of 1,3,5-triethynylbenzene, the dosage of dopamine hydrochloride, and the coating time, etc. (In order to ensure reasonable electrical conductivity of the material and have high wave-absorbing performance, the thickness of the nitrogen-doped carbon layer is 60 - 85 nm, and the thickness of the hydrogenated graphdiyne layer is 5 - 13 nm). The wave-absorbing agent prepared by this method has the advantages of a hollow three-layer core-shell structure, multi-component composite, and one-dimensional material. It is not only a one-dimensional structure with pores (pores can be formed during the carbonization of polydopamine, and the hollow of the carbon nanotubes can achieve the superposition of effects together) and a large aspect ratio, but also lightweight, with a high specific surface area, high porosity, rich heterogeneous interfaces, and N atom doping, and has relatively excellent wave-absorbing performance, and has potential application value in fields such as radio communication systems and radar stealth technology. Description of the Drawings
[0047] Figure 1 is a schematic diagram of the preparation process of the CNTs@PDA@HsGDY nanofiber-derived wave-absorbing agent;
[0048] Figure 2 is a transmission electron microscope photograph of the CNTs@PDA@HsGDY nanofiber-derived wave-absorbing agent;
[0049] Figure 3 is the loss curve of the CNTs@PDA@HsGDY nanofiber-derived wave-absorbing agent. Detailed implementation manners
[0050] The content of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments:
[0051] As Figure 1 shown, the preparation method of the CNTs@PDA@HsGDY nanofiber-derived microwave absorbing agent includes the following steps:
[0052] 1) Ultrasonically disperse carbon nanotubes in a Tris-HCl buffer solution with pH = 8.3 - 8.7 to obtain suspension A; in suspension A, the mass concentration of carbon nanotubes is 0.5 - 1 mg / mL; the carbon nanotubes are single-walled or multi-walled carbon nanotubes with carboxyl or hydroxyl groups on the surface; among them, the hydroxyl content is higher than 1.5 wt%, and the hydroxyl content is higher than 2 wt%;
[0053] 2) Under magnetic stirring, add the Tris-HCl buffer solution containing dopamine hydrochloride with pH = 8.3 - 8.7 to suspension A obtained in step 1), react at room temperature for 24 - 48 h, and after the reaction is completed, centrifuge and separate, wash with ethanol, and vacuum dry to obtain CNTs@PDA nanotubes;
[0054] The mass concentration of dopamine hydrochloride is 1 - 3 mg / mL, and the mass ratio of carbon nanotubes to dopamine hydrochloride is 1:2 - 5;
[0055] 3) Mix the CNTs@PDA nanotubes obtained in step 2) with solvent I and solvent II, and ultrasonically disperse them evenly to obtain suspension B;
[0056] Solvent I is tetrahydrofuran or pyridine; solvent II is trimethylamine or triethylamine; the volume ratio of solvent I to solvent II is 1:1 - 3, and in suspension B, the mass concentration of CNTs@PDA nanotubes is 0.1 - 0.5 mg / mL;
[0057] 4) Under the protection of inert gas, add 1,3,5-triethynylbenzene, catalyst I and catalyst II to suspension B obtained in step 3), react at room temperature for 48 - 64 h under magnetic stirring, and after the reaction is completed, centrifuge and separate, wash with ethanol, and vacuum dry to obtain CNTs@PDA@HsGDY nanofibers;
[0058] Catalyst I is bis(triphenylphosphine)palladium dichloride or tetrakis(triphenylphosphine)palladium; catalyst II is copper iodide, copper bromide or copper chloride; the molar ratio of 1,3,5-triethynylbenzene, catalyst I and catalyst II is 3∶1∶1; the mass ratio of 1,3,5-triethynylbenzene to CNTs@PDA nanotubes is 1:8 - 10;
[0059] 5) The CNTs@PDA@HsGDY nanofibers obtained in step 4) were vacuum carbonized in a tube furnace at 600 - 900 °C for 1 - 3 h, with the heating rate controlled at 1 - 5 °C / min, to obtain the product CNTs@PDA@HsGDY nanofiber derivative CNTs@NC@HsGDY.
[0060] The inert gas described above is nitrogen or argon.
[0061] The following are specific examples:
[0062] Example 1:
[0063] Weigh 30 mg of single-walled carbon nanotubes (with a carboxyl group content below 1.5 wt% and a hydroxyl group content above 2 wt%) into a single-neck flask, and ultrasonically disperse them in 50 mL of Tris-HCl buffer solution with pH = 8.5 to obtain a suspension. Under magnetic stirring, 100 mL of Tris-HCl buffer solution containing 100 mg of dopamine hydrochloride was added to the suspension, and the reaction was carried out at room temperature for 24 h. After centrifugal separation, it was washed with ethanol and dried in vacuum to obtain CNTs@PDA nanotubes. Weigh 40 mg of CNTs@PDA nanotubes, add 50 mL of tetrahydrofuran and 150 mL of trimethylamine, and ultrasonically disperse them to make a uniform suspension, obtaining a CNTs@PDA nanotube suspension. Under the protection of an inert gas, 5 mg of 1,3,5-triethynylbenzene, 7.8 mg of bis(triphenylphosphine)palladium dichloride, and 2.1 mg of cuprous bromide were added to the CNTs@PDA nanotube suspension, and the reaction was carried out at room temperature for 48 h under magnetic stirring. After centrifugal separation, it was washed with ethanol and dried in vacuum to obtain CNTs@PDA@HsGDY nanofibers. The CNTs@PDA@HsGDY nanofibers were vacuum carbonized in a tube furnace at 700 °C for 2 h, with the heating rate controlled at 5 °C / min, to obtain the product CNTs@NC@HsGDY one-dimensional microwave absorber.
[0064] It can be seen from Figure 2 that as a whole, it presents a three-layer core-shell structure, from the inside to the outside are carbon nanotubes, nitrogen-doped carbon layer, and hydrogenated graphdiyne layer in sequence, and its inner diameter and length are the same as those of the selected carbon nanotubes; they are intertwined to form a three-dimensional network structure.
[0065] Example 2:
[0066] Weigh 50 mg of double-walled carbon nanotubes (carboxyl group content less than 1.5 wt%, hydroxyl group content more than 2 wt%) into a single-necked flask, and ultrasonically disperse them in 60 mL of Tris-HCl buffer solution with pH = 8.4 to obtain a suspension. Under magnetic stirring, add 75 mL of Tris-HCl buffer solution containing 150 mg of dopamine hydrochloride to the suspension, react at room temperature for 36 h, centrifuge, wash with ethanol, and vacuum dry to obtain CNTs@PDA nanotubes. Weigh 60 mg of CNTs@PDA nanotubes, add 50 mL of pyridine and 100 mL of trimethylamine, and ultrasonically disperse them evenly to obtain a CNTs@PDA nanotube suspension. Under inert gas protection, add 7.5 mg of 1,3,5-triethynylbenzene, 19.3 mg of tetrakis(triphenylphosphine)palladium, and 3.2 mg of copper iodide to the CNTs@PDA nanotube suspension, react at room temperature for 60 h under magnetic stirring, centrifuge, wash with ethanol, and vacuum dry to obtain CNTs@PDA@HsGDY nanofibers. Carbonize the CNTs@PDA@HsGDY nanofibers in a tube furnace at 600 °C under vacuum for 3 h, controlling the heating rate at 2 °C / min to obtain the product CNTs@NC@HsGDY one-dimensional microwave absorber.
[0067] Example 3:
[0068] Weigh 40 mg of double-walled carbon nanotubes (carboxyl group content less than 1.5 wt%, hydroxyl group content more than 2 wt%) into a single-necked flask, and ultrasonically disperse them in 40 mL of Tris-HCl buffer solution with pH = 8.3 to obtain a suspension. Under magnetic stirring, add 100 mL of Tris-HCl buffer solution containing 200 mg of dopamine hydrochloride to the suspension, react at room temperature for 40 h, centrifuge, wash with ethanol, and vacuum dry to obtain CNTs@PDA nanotubes. Weigh 60 mg of CNTs@PDA nanotubes, add 80 mL of tetrahydrofuran and 80 mL of trimethylamine, and ultrasonically disperse them evenly to obtain a CNTs@PDA nanotube suspension. Under inert gas protection, add 6 mg of 1,3,5-triethynylbenzene, 9.4 mg of bis(triphenylphosphine)palladium dichloride, and 1.9 mg of copper bromide to the CNTs@PDA nanotube suspension, react at room temperature for 64 h under magnetic stirring, centrifuge, wash with ethanol, and vacuum dry to obtain CNTs@PDA@HsGDY nanofibers. Carbonize the CNTs@PDA@HsGDY nanofibers in a tube furnace at 800 °C under vacuum for 2 h, controlling the heating rate at 5 °C / min to obtain the product CNTs@NC@HsGDY one-dimensional microwave absorber.
[0069] Example 4:
[0070] Weigh 60 mg of single-walled carbon nanotubes (carboxyl group content less than 1.5 wt%, hydroxyl group content more than 2 wt%) into a single-necked flask, and ultrasonically disperse them in 75 mL of Tris-HCl buffer solution with pH = 8.6 to obtain a suspension. Under magnetic stirring, add 150 mL of Tris-HCl buffer solution containing 180 mg of dopamine hydrochloride to the suspension, react at room temperature for 24 h, centrifuge and wash with ethanol, and vacuum dry to obtain CNTs@PDA nanotubes. Weigh 70 mg of CNTs@PDA nanotubes, add 35 mL of pyridine and 105 mL of triethylamine, and ultrasonically disperse them evenly to obtain a CNTs@PDA nanotube suspension. Under the protection of inert gas, add 8 mg of 1,3,5-triethynylbenzene, 12.5 mg of bis(triphenylphosphine)palladium dichloride and 3.4 mg of copper iodide to the CNTs@PDA nanotube suspension, react at room temperature for 54 h under magnetic stirring, centrifuge and wash with ethanol, and vacuum dry to obtain CNTs@PDA@HsGDY nanofibers. Carbonize the CNTs@PDA@HsGDY nanofibers in a tube furnace at 900 °C under vacuum for 3 h, and control the heating rate at 2 °C / min to obtain the product CNTs@NC@HsGDY one-dimensional microwave absorber.
[0071] Example 5:
[0072] Weigh 40 mg of multi-walled carbon nanotubes (carboxyl group content less than 1.5 wt%, hydroxyl group content more than 2 wt%) into a single-necked flask, and ultrasonically disperse them in 50 mL of Tris-HCl buffer solution with pH = 8.4 to obtain a suspension. Under magnetic stirring, add 110 mL of Tris-HCl buffer solution containing 160 mg of dopamine hydrochloride to the suspension, react at room temperature for 36 h, centrifuge and wash with ethanol, and vacuum dry to obtain CNTs@PDA nanotubes. Weigh 60 mg of CNTs@PDA nanotubes, add 50 mL of pyridine and 100 mL of trimethylamine, and ultrasonically disperse them evenly to obtain a CNTs@PDA nanotube suspension. Under the protection of inert gas, add 6 mg of 1,3,5-triethynylbenzene, 15.4 mg of tetrakis(triphenylphosphine)palladium and 1.3 mg of copper chloride to the CNTs@PDA nanotube suspension, react at room temperature for 56 h under magnetic stirring, centrifuge and wash with ethanol, and vacuum dry to obtain CNTs@PDA@HsGDY nanofibers. Carbonize the CNTs@PDA@HsGDY nanofibers in a tube furnace at 800 °C under vacuum for 3 h, and control the heating rate at 4 °C / min to obtain the product CNTs@NC@HsGDY one-dimensional microwave absorber.
[0073] Example 6:
[0074] Weigh 50 mg of multi-walled carbon nanotubes (with carboxyl group content less than 1.5 wt% and hydroxyl group content higher than 2 wt%) into a single-necked flask, and ultrasonically disperse them in 60 mL of Tris-HCl buffer solution with pH = 8.6 to obtain a suspension. Under magnetic stirring, add 80 mL of Tris-HCl buffer solution dissolved with 100 mg of dopamine hydrochloride to the suspension, react at room temperature for 24 h, centrifuge and wash with ethanol, and vacuum dry to obtain CNTs@PDA nanotubes. Weigh 70 mg of CNTs@PDA nanotubes, add 40 mL of tetrahydrofuran and 120 mL of triethylamine, and ultrasonically disperse them to make them uniformly dispersed to obtain a CNTs@PDA nanotube suspension. Under the protection of inert gas, add 7 mg of 1,3,5-triethynylbenzene, 10.9 mg of bis(triphenylphosphine)palladium dichloride and 1.5 mg of copper chloride to the CNTs@PDA nanotube suspension, react at room temperature for 64 h under magnetic stirring, centrifuge and wash with ethanol, and vacuum dry to obtain CNTs@PDA@HsGDY nanofibers. Carbonize the CNTs@PDA@HsGDY nanofibers in a tube furnace at 900 °C under vacuum for 2 h, and control the heating rate at 2 °C / min to obtain the product CNTs@NC@HsGDY one-dimensional microwave absorber.
[0075] Example 7:
[0076] Weigh 60 mg of single-walled carbon nanotubes (with carboxyl group content less than 1.5 wt% and hydroxyl group content higher than 2 wt%) into a single-necked flask, and ultrasonically disperse them in 65 mL of Tris-HCl buffer solution with pH = 8.5 to obtain a suspension. Under magnetic stirring, add 120 mL of Tris-HCl buffer solution dissolved with 180 mg of dopamine hydrochloride to the suspension, react at room temperature for 40 h, centrifuge and wash with ethanol, and vacuum dry to obtain CNTs@PDA nanotubes. Weigh 80 mg of CNTs@PDA nanotubes, add 60 mL of tetrahydrofuran and 120 mL of trimethylamine, and ultrasonically disperse them to make them uniformly dispersed to obtain a CNTs@PDA nanotube suspension. Under the protection of inert gas, add 9 mg of 1,3,5-triethynylbenzene, 23.1 mg of tetrakis(triphenylphosphine)palladium and 3.8 mg of copper iodide to the CNTs@PDA nanotube suspension, react at room temperature for 60 h under magnetic stirring, centrifuge and wash with ethanol, and vacuum dry to obtain CNTs@PDA@HsGDY nanofibers. Carbonize the CNTs@PDA@HsGDY nanofibers in a tube furnace at 700 °C under vacuum for 3 h, and control the heating rate at 5 °C / min to obtain the product CNTs@NC@HsGDY one-dimensional microwave absorber.
[0077] In addition, the present invention also detected the microwave absorption performance of the target product, such as Figure 3As shown in the loss curve, the minimum reflection loss of the target product is -46.88 dB, the effective absorption bandwidth is 5.6 GHz, and the filler content is 7.5%. It can be seen that the CNTs@PDA@HsGDY nanofiber derivative designed in the present invention, namely CNTs@NC@HsGDY, adds a layer of nitrogen-doped carbon in the middle on the basis of the previous scheme. The addition of this organic layer has little effect on the minimum reflection loss and effective absorption bandwidth of the composite material, and the filler content is significantly reduced compared with the previous scheme (the minimum reflection loss is -47.14 dB, the effective absorption bandwidth is 5.9 GHz, and the filler content is 9%). That is to say, under the condition of taking into account the minimum reflection loss and effective absorption bandwidth, the impedance matching of the present invention is better, and almost the same effect can be achieved with a very small filler content, realizing further optimization. At the same time, the types of wave-absorbing agents are enriched, and it has good application prospects and competitiveness. It can be used as a wave-absorbing filler to prepare devices with radar stealth functions.
[0078] The above is only the specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention can easily think of various equivalent modifications or substitutions, and these modifications or substitutions should all be covered within the protection scope of the present invention.
Claims
1. A kind of CNTs@PDA@HsGDY nanofiber derivative, characterized in that: It presents a three-layer core-shell structure as a whole. From the inside to the outside, it is a carbon nanotube, a nitrogen-doped carbon layer, and a hydrogenated graphdiyne layer in sequence. The inner diameter and length of the CNTs@PDA@HsGDY nanofiber derivative are the same as those of the selected carbon nanotubes. The thickness of the nitrogen-doped carbon layer is 60 - 85 nm, and the thickness of the hydrogenated graphdiyne layer is 5 - 13 nm. The carbon nanotubes are single-walled or multi-walled carbon nanotubes with carboxyl or hydroxyl groups on the surface; among them, the carboxyl content is higher than 1.5 wt%, and the hydroxyl content is higher than 2 wt%.
2. The preparation method of the CNTs@PDA@HsGDY nanofiber derivative according to claim 1, characterized in that, It includes the following steps: 1) Disperse the carbon nanotubes in a buffer solution with pH = 8.3 - 8.7 to obtain suspension A; The carbon nanotubes are single-walled or multi-walled carbon nanotubes with carboxyl or hydroxyl groups on the surface; among them, the carboxyl content is higher than 1.5 wt%, and the hydroxyl content is higher than 2 wt%; 2) Under stirring, add the buffer solution containing hydrochloric acid dopamine with pH = 8.3 - 8.7 to the suspension A obtained in step 1), react at room temperature, after the reaction is completed, centrifuge, wash, and vacuum dry to obtain CNTs@PDA nanotubes; 3) Mix the CNTs@PDA nanotubes obtained in step 2) with solvent I and solvent II, and make them evenly dispersed to obtain suspension B; The solvent I is tetrahydrofuran or pyridine; The solvent II is trimethylamine or triethylamine; 4) Under the protection of inert gas, add 1,3,5-triethynylbenzene, catalyst I, and catalyst II to the suspension B obtained in step 3), react at room temperature under stirring, after the reaction is completed, centrifuge, wash, and vacuum dry to obtain CNTs@PDA@HsGDY nanofibers; The catalyst I is a palladium catalyst in the form of a complex; The catalyst II is a cuprous halide catalyst; 5) Vacuum carbonize the CNTs@PDA@HsGDY nanofibers obtained in step 4) to obtain the product CNTs@PDA@HsGDY nanofiber derivative CNTs@NC@HsGDY.
3. The preparation method of the CNTs@PDA@HsGDY nanofiber derivative according to claim 2, characterized in that: In step 1), the buffer solution is a Tris hydrochloride buffer solution with pH = 8.3 - 8.7; In suspension A, the mass concentration of carbon nanotubes is 0.5 - 1 mg / mL.
4. The preparation method of the CNTs@PDA@HsGDY nanofiber derivative according to claim 2 or 3, characterized in that: The buffer solution used in step 2) is a Tris hydrochloride buffer solution with pH = 8.3 - 8.7; the mass concentration of hydrochloric acid dopamine is 1 - 3 mg / mL; The mass ratio of carbon nanotubes to hydrochloric acid dopamine is 1:2 - 5; The reaction time at room temperature is 24 - 48 h; After the reaction is completed, wash with ethanol.
5. The preparation method of the CNTs@PDA@HsGDY nanofiber derivative according to claim 4, characterized in that: In step 3), the volume ratio of solvent I to solvent II is 1:1 - 3; In suspension B, the mass concentration of CNTs@PDA nanotubes is 0.1 - 0.5 mg / mL.
6. The preparation method of the CNTs@PDA@HsGDY nanofiber derivative according to claim 5, characterized in that: In step 4), the catalyst I is bis(triphenylphosphine)palladium dichloride or tetrakis(triphenylphosphine)palladium; The catalyst II is copper(I) iodide, copper(I) bromide or copper(I) chloride; The molar ratio of 1,3,5-triethynylbenzene, catalyst I and catalyst II is 3∶1∶1; The mass ratio of 1,3,5-triethynylbenzene to the CNTs@PDA nanotubes is 1:8 - 10; React at room temperature for 48 - 64 h under magnetic stirring; After the reaction is completed, wash with ethanol.
7. The preparation method of the CNTs@PDA@HsGDY nanofiber derivative according to claim 6, characterized in that, Step 5) is specifically: Vacuum carbonize the CNTs@PDA@HsGDY nanofibers obtained in step 4) in a tube furnace at 600 - 900 °C for 1 - 3 h, and control the heating rate to be 1 - 5 °C / min to obtain the product CNTs@PDA@HsGDY nanofiber derivative CNTs@NC@HsGDY.
8. The application of the CNTs@PDA@HsGDY nanofiber derivative according to claim 1 as a wave-absorbing agent.
9. A device with radar stealth function, characterized in that: It uses the CNTs@PDA@HsGDY nanofiber derivative CNT@NCs@HsGDY according to claim 1 as a wave-absorbing agent for filling.
Citation Information
Patent Citations
Preparation method of chitosan modified barium ferrite filling multi-walled carbon nanotube / poly 3-methylthiophene composite wave-absorbing material
CN102627834B
A cerium-doped nickel-zinc ferrite-filled carbon nanotube composite absorbing material and its preparation
CN104945759B
A porous carbon@carbon nanotube microwave absorbing material and its preparation method
CN109880591B
A lightweight hollow carbon cube microwave absorbing material and its preparation method
CN110950320B
A carbon nanotube-aluminum nitride microwave absorbing agent and its preparation method, a carbon nanotube-aluminum nitride composite microwave absorbing material and its application
CN111205819B